Translanguaging practices and teacher perspectives in a CLIL program: A case study at a national plus school in Indonesia - Khafshoh, Adira Lizaria; Anugerahwati, Mirjam; Yannuar, Nurenzia; Basthomi, Yazid (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
The increasing adoption of content and language integrated learning (CLIL) in educational settings has caught teachers’ interest in using translanguaging as a tool to promote effective teaching and learning. Many studies have discussed translanguaging in CLIL, but limited studies have focused on young learners. This case study aims to explore translanguaging practices and perspectives in the CLIL context. Three teachers at one of the national plus schools in Malang, Indonesia, participated in this study. The data were obtained from classroom observations and interviews and analyzed using a thematic pattern. The results showed that teachers’ teaching practices, if seen from a translanguaging lens, while they were explaining the material, asking questions, giving tasks, and giving feedback to young learners. The reasons why the teachers applied translanguaging were to explain the materials and give advice to students, and to address students’ multilingual backgrounds. The advantages of performing translanguaging were to understand the instruction, explain the difficult materials, bond with students, and improve students’ vocabulary. This study suggests that integrating translanguaging strategies in CLIL might support more inclusive and effective teaching for young multilingual learners.